IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR (SOP) PADA PENERIMAAN SISWA BARU SMA N 1 KEPAHIANG DALAM MEWUJUDKAN OUT PUT YANG BERKUALITAS - Mashuri Renoldi (IAIN Bengkulu, 2018)
The results of this study are Based on this research, data processing, and data analysis that researchers do related to the analysis of input factors, nThis, otput, and outcome in the implementation of School Based Management (SBM) at SMAN1 Kepahiang, the writer can conclude the following points related with this research that the presence of input also is not ‘up’ because in reality there are some inputs that have not reached the SNP, for example on the number of students in rombel. The education process in SMAN 1 Kepahiang summarized in the school management process that seeks to involve the entire school community to support the PBM. Curriculum development at SMAN 1 Kepahiang seek to maximize the PBM in order to become qualified. However PBM is not maximized because they have constraints on the availability of facilities and infrastructure. The existence of output factors, in accordance with the SNP hopes that maximizes all the competences of the learners. But in fact the intended target are often distorted by the fact that happened